The National Environmental Policy Act: A Review of Its Experience and Problems - Daniel R. Mandelker (Washington University Journal of Law & Policy, 2010)
The National Environmental Policy Act (“NEPA”), the Magna Carta of environmental law, requires all federal agencies to evaluate the environmental impacts of their actions, a duty that extends to state, local, and private entities when a federal link is present. This Article looks at major elements in NEPA's implementation and the major contributions NEPA has made to environmental analysis. It reviews strengths and weaknesses and suggests where improvement can occur as NEPA moves forward as a protector of environmental values. The Article's focus is on encouraging agencies to take a wider view of the environmental impacts they consider in a decision making process that is less confining than the process now in place. Part I begins the analysis by reviewing NEPA’s record as an environmental statute, noting achievements the statute has attained and criticisms it has attracted. Part II reviews the NEPA decision making process, assessing whether it has been effective as a means of carrying out NEPA’s environmental mandate. Part III considers how NEPA applies to agency projects as compared with agency plans and programs, and how NEPA’s effectiveness differs in these two settings. Part IV considers the “heart” of the environmental impact statement, the duty to consider alternatives to a proposed action, and how the courts have interpreted this requirement. Part V examines agency duties to extend their environmental analysis beyond the proposal under review by considering its indirect impacts. Part VI concludes by asking, in view of this discussion, whether NEPA has met the environmental challenge the statute was intended to meet.
Keywords: Government agencies; Decision making; Environmental policy; Judicial review of administrative acts; Environmental impact statements; Environmental management; National Environmental Policy Act of 1969